Asksia AI LOGO

Sia

Question
Math
Posted 9 months ago

Let
A=[171226218]
A=\left[\begin{array}{ccc}
1 & -7 & -1 \\
2 & -2 & 6 \\
-2 & -1 & -8
\end{array}\right] \text {. }


Find an orthonormal basis of the column space of AA. \{[]],
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 1
To find an orthonormal basis of the column space of matrix AA, we first need to orthogonalize the columns of AA. The matrix AA is given by: A=[171226218] A = \begin{bmatrix} 1 & -7 & -1 \\ 2 & -2 & 6 \\ -2 & -1 & -8 \end{bmatrix} We will use the Gram-Schmidt process to orthogonalize the columns
step 2
Let v1=[122]\mathbf{v}_1 = \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix}, v2=[721]\mathbf{v}_2 = \begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix}, and v3=[168]\mathbf{v}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix}. We start with u1=v1\mathbf{u}_1 = \mathbf{v}_1
step 3
Next, we compute u2\mathbf{u}_2 by subtracting the projection of v2\mathbf{v}_2 onto u1\mathbf{u}_1 from v2\mathbf{v}_2: u2=v2v2u1u1u1u1 \mathbf{u}_2 = \mathbf{v}_2 - \frac{\mathbf{v}_2 \cdot \mathbf{u}_1}{\mathbf{u}_1 \cdot \mathbf{u}_1} \mathbf{u}_1 u2=[721][721][122][122][122][122] \mathbf{u}_2 = \begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix} - \frac{\begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix} \cdot \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix}}{\begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} \cdot \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix}} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} u2=[721]7+(4)+21+4+4[122] \mathbf{u}_2 = \begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix} - \frac{-7 + (-4) + 2}{1 + 4 + 4} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} u2=[721]99[122] \mathbf{u}_2 = \begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix} - \frac{-9}{9} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} u2=[721]+[122] \mathbf{u}_2 = \begin{bmatrix} -7 \\ -2 \\ -1 \end{bmatrix} + \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} u2=[603] \mathbf{u}_2 = \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix}
step 4
Now, we compute u3\mathbf{u}_3 by subtracting the projections of v3\mathbf{v}_3 onto u1\mathbf{u}_1 and u2\mathbf{u}_2 from v3\mathbf{v}_3: u3=v3v3u1u1u1u1v3u2u2u2u2 \mathbf{u}_3 = \mathbf{v}_3 - \frac{\mathbf{v}_3 \cdot \mathbf{u}_1}{\mathbf{u}_1 \cdot \mathbf{u}_1} \mathbf{u}_1 - \frac{\mathbf{v}_3 \cdot \mathbf{u}_2}{\mathbf{u}_2 \cdot \mathbf{u}_2} \mathbf{u}_2 u3=[168][168][122][122][122][122][168][603][603][603][603] \mathbf{u}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} - \frac{\begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} \cdot \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix}}{\begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} \cdot \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix}} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} - \frac{\begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} \cdot \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix}}{\begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} \cdot \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix}} \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} u3=[168]1+12+169[122]6+2445[603] \mathbf{u}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} - \frac{-1 + 12 + 16}{9} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} - \frac{6 + 24}{45} \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} u3=[168]279[122]3045[603] \mathbf{u}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} - \frac{27}{9} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} - \frac{30}{45} \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} u3=[168]3[122]23[603] \mathbf{u}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} - 3 \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} - \frac{2}{3} \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} u3=[168][366]+[402] \mathbf{u}_3 = \begin{bmatrix} -1 \\ 6 \\ -8 \end{bmatrix} - \begin{bmatrix} 3 \\ 6 \\ -6 \end{bmatrix} + \begin{bmatrix} 4 \\ 0 \\ 2 \end{bmatrix} u3=[13+466+08+6+2] \mathbf{u}_3 = \begin{bmatrix} -1 - 3 + 4 \\ 6 - 6 + 0 \\ -8 + 6 + 2 \end{bmatrix} u3=[000] \mathbf{u}_3 = \begin{bmatrix} 0 \\ 0 \\ 0 \end{bmatrix} Since u3\mathbf{u}_3 is the zero vector, it does not contribute to the basis
step 5
Now, we normalize u1\mathbf{u}_1 and u2\mathbf{u}_2 to get the orthonormal basis vectors: e1=u1u1=13[122]=[132323] \mathbf{e}_1 = \frac{\mathbf{u}_1}{\|\mathbf{u}_1\|} = \frac{1}{3} \begin{bmatrix} 1 \\ 2 \\ -2 \end{bmatrix} = \begin{bmatrix} \frac{1}{3} \\ \frac{2}{3} \\ -\frac{2}{3} \end{bmatrix} e2=u2u2=145[603]=[25015] \mathbf{e}_2 = \frac{\mathbf{u}_2}{\|\mathbf{u}_2\|} = \frac{1}{\sqrt{45}} \begin{bmatrix} -6 \\ 0 \\ -3 \end{bmatrix} = \begin{bmatrix} -\frac{2}{\sqrt{5}} \\ 0 \\ -\frac{1}{\sqrt{5}} \end{bmatrix}
Answer
The orthonormal basis of the column space of AA is $\left\{ \begin{bmatrix} \frac{1}{3} \\ \frac{2}{3} \\ -\frac{2}{3} \end{bmatrix}, \begin{bmatrix} -\frac{2}{\sqrt{5}} \\ 0 \\ -\frac{1}{\sqrt{5}} \end{bmatrix} \right\}
Key Concept
Orthonormal Basis
Explanation
An orthonormal basis of a vector space is a set of vectors that are both orthogonal and normalized. The Gram-Schmidt process is used to orthogonalize a set of vectors, and then each vector is normalized to form the orthonormal basis.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question